Navigating climate's human geographies: Exploring the whereabouts of climate politics. Issue 1 (March 2019) - Bulkeley, Harriet
Just as global institutions and environmental assessment processes embark on the latest effort to integrate more social science into global environmental change research, it appears that the social sciences of climate change are unable or unwilling to address this challenge. In this article, I explore the nature of these dynamics within human geography and argue that climate change occupies a curiously ambiguous position within our discipline of both an explicit presence and an underlying absence. Framed predominantly in terms of a biophysical challenge requiring some form of social response, work on climate change retains an assumed socio-nature divide – a position which has yet to be substantively challenged by the different strands of political ecology, new materialism and environmental humanities that now pervade the discipline. To advance new geographies of climate change, the article argues that our understanding of climate change needs to shift from that of a problem that needs specific responses to a condition that is constituted through specific forms of socio-spatial relation and in turn constitutes the politics, ethics and meaning of particular socio-spatial orderings, from the citizen to the city, the community to the corporation.